Comparative Analysis of Implementation of 6PE and 6VPE Methods on MPLS Network - Nugroho, Kukuh; Lanza, Bimo Kusdamarsasi; Wahyudi, Eka (Universitas Islam Sumatera Utara, 2022)
The growth of Internet users and services such as video streaming and big data application make particular problems in the core network such as the depletion of IPv4 allocation, delay, and jitter. MPLS as technology in the core network is used for anticipating delay problems due to data traffic improvement on the Internet. To anticipate the growth of Internet users and the depletion of IPv4 allocation as an address to access the network, it needs the new version of IP that is IPv6 with a bigger amount of address allocation. The incorporation of those addressing mechanisms in the core network needs a particular method to exchange data between devices. This research compares two translation methods between 6PE and 6VPE in the MPLS-VPN network. The result of measurement of throughput shows that the use of the 6VPE method provides better efficiency of network used 15% than 6PE in the data rate of 2000 Kbps. The experiment is done by comparing the two methods in the MPLS-VPN network with only using the IPv4 addressing mechanism where the service used is video streaming.